The Maladministration of Public Security - Gledhill, John (Revista de Antropología Social, 2013)
This paper examines public policies based on the idea that situations in areas of social deprivation threaten the security of all other urban residents. Using evidence from São Paulo, Rio de Janeiro and Salvador, the three biggest metropolitan cities of Brazil, where mano dura approaches frequently enjoy popular support, and significant reductions in poverty and social inequality have not reduced crime and violence, the analysis demonstrates the counter-productive consequences of simple policies of repression, especially in the context of a neoliberal model of urban development based on “accumulation by dispossession” and a privatization of public power that militates against the success of police reform. The paper explores ways in which, despite new commitments to deliver social justice, the state remains part of the problem, together with the implications of differences in the organization of drug trafficking and the alternative forms of “pacification” offered by “the rule of crime”. Criticizing a politics of securitization that prioritizes a theatrical war on delinquency that criminalizes poverty and drug addiction, the text argues for democratizing the production of public security policies, understanding what kinds of security poor people prioritize, such as security against eviction, and devoting more public resources to improving the police career.